ANALISIS HUBUNGAN INDEKS BIAS DAN INTENSITAS CAHAYA PADA BERBAGAI FLUIDA - Muhammad Akbar Mukhlis; Albertus Djoko Lesmono; Lailatul Nuraini (JURNAL PEMBELAJARAN FISIKA, 2021)
This research aimed to examine the relationship between refractive index and light intensity in various fluids. This type of this research was experimental research. The measurement data obtained the refractive index values of various fluids, namely the refractive index of spirit, watered, alcohol, oil, and oil respectively 1. 3066 ± 0. 0053, 1. 319 ± 0. 0056, 1. 3422 ± 0. 0061, 1. 438 ± 0. 0054, 1. 576 ± 0. 0068. The data from the measurement of light intensity in various fluids obtained the valued of the intensity of light that passed through spirit, watered, alcohol, oil, and oil, respectively, namely 1220. 8 ± 3. 72 lux, 1219 ± 3. 9 lux, 1216. 2 ± 3, 77 lux, 1202. 6 ± 3. 88 lux, and 1180. 2 ± 4. 07 lux. The results of this research obtained a valued of r = 1 which indicates that the relationship between the refractive index and light intensity was very strong. The conclusion in this studied was that there was a relationship between refractive index and light intensity. This relationship could been seen in the refractive index, the greater the valued in the fluid would made the transmitted light intensity decrease or inversely proportional. Key word: fluid, light intensity, refractive index